MARKETING STRATEGY ANALYSIS USING THE METHOD SWOT AND QSPM IN INDUSTRIAL SCREEN PRINTING INDUSTRIES - Septiyan Adi Saputro; eli Mas'idah; Andre Sugiyono (Universitas Islam Sultan Agung, 2021)
Omah Sablon is a company engaged in screen printing. As a company engaged in screen printing, Omah Sablon must be more creative in designing and deciding business missions and marketing strategies that will be applied in the field to be able to anticipate various kinds of changes that will occur. Companies can continue to compete and move in the direction of consumer desires, because basically the company's function is to produce goods and services that can be accepted by consumers as well as to meet consumer desires. The number of sales that have not been stable causes the profits obtained by the company to not reach the target as desired by the company. That is because the production or ordering process from omah screen printing consumers occurs seasonally. Therefore it is necessary to analyze the marketing strategy to increase sales results. In the analysis of marketing strategies Omah Sablon is carried out using the Strength Weakness Opportunity Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM) methods. The first step is filling out internal and external factor questionnaires which are then analyzed using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, with values of IFE 2.69 and EFE 2.31, which are entered into the Grand Strategy matrix and known to the company located in quadrant I (has a perfect strategic position). Furthermore SWOT analysis to produce alternative strategies. Then from the Grand Strategy matrix analysis can draw conclusions to use the most interesting strategy to be analyzed using QSPM. Then from the results of the QSPM matrix it can be concluded that the most appropriate marketing strategy used by Omah Sablon to increase sales is Procurement of QC systems in the production process as a guarantor of product quality, Carrying out marketing programs with canvassing systems and also online systems in downtown Ungaran and providing fast service. and easy and add product variants.